Near-Field Transmission-Type Microwave Imaging for Noninvasive Evaluation of Electromagnetic Characteristics: Toward Early Breast Tumor Detection - Shanwen Luo; Zhong Ji; Sihua Yang; Da Xing (IEEE Photonics Journal)
A near-field transmission-type microwave imaging (NTMI) system was developed to break the bottleneck of the resolution of microwave imaging due to diffraction limitation. The NTMI used a microwave pinhole to control the size of microwave radiation in the near-field region and a high-resolution and highly sensitive detector based on electromagnetic-elastic resonance effect to acquire the transmitted microwave signal. The theoretical analysis and experimental validation showed that the resolution of the NTMI system was up to 1.55 mm, higher than the current resolution (∼cm) of microwave imaging. And the contrast of microwave transmittance based on the different electromagnetic characteristics among various tissues was theoretically deduced and experimentally examined. Moreover, a breast phantom was imaged to estimate the imaging capability of the NTMI system with high contrast (3.7:1–16.7:1) and good tissue penetration (>10 cm). Finally, the excised breast of an ewe embedded with an ex vivo human breast tumor was imaged clearly with a contrast of about 1:2.8, which is in good agreement with the X-ray image. Therefore, the NTMI system is suitable for noninvasive mass screening and has a great potential for applications in early breast cancer detection.